Pengaruh Perbandingan Tepung Pisang Kepok (Musa paradisiaca normalis) dan Tepung Wortel (Daucus carota) Terhadap Karakteristik Kukis - Kusumaning Ayu, Made Ardha; Yusasrini, Ni Luh Ari; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i02.p08, 2024)
Cookies are cakes made from a mixture of wheat flour, powdered sugar, margarine and egg yolks, then baked. Usually dry cakes have a soft texture with a sweet or salty taste. Compared to cookies, cookies have a different shape, cookies are also softer because of the use of butter and eggs. There are many types of biscuits on the market with flour substitutes made from local raw materials such as mocaf flour and tapioca flour, but the use of kepok banana flour and carrot flour as substitute ingredients for biscuits has not yet been discovered. This research aims to determine the effect and correct comparison between Banana Kepok flour and Carrot flour to get the best properties in cookies. The model used in this research was a Completely Randomized Design (CRD) with a comparison treatment between banana flour and carrot flour consisting of 6 levels, namely 100%:0%, 90%:10%, 80%:20%, 70%:30 %, 60%:40% and 50%:50%. All treatments were repeated three times to produce 18 experimental units. The data obtained were analyzed using Anova and then using Duncan's Multiple Range Test (DMRT). The analysis results showed that the comparison of banana flour and carrot flour had a significant effect on the properties of cookies (P<0.05), especially ash content, water content, protein content, fat content, carbohydrate content, firmness, and beta-carotene content. , aroma, taste, color, texture and overall acceptability. The best biscuit properties were obtained by processing 80% banana powder and 20% carrot powder with a hardness value of 20.79 N, ash content of 2.56%, water content of 1.40%, fat content of 26.53%, protein content of 3.0, 90%, carbohydrate content 65.61 % and beta-carotene content 1.79 mg/100 g and the sensory characteristics of aroma, color Color, taste, texture and overall acceptability are all liked.